Elucidating the effect of Ce/Zr ratio on high temperature shift activity with sulfur poisoning - 김경진; 전경원; 홍가람; 전병훈; 배종욱; 장원준; 이열림; 노현석 (Journal of Industrial and Engineering Chemistry, 2022)
To elucidate the effect of CeO2/ZrO2 ratio on the sulfur-tolerance in high temperature shift using wastederived synthesis gas, the Ce/Zr ratio in Pt/CexZr1-xO2 catalysts was systematically changed. Pt/CexZr1-xO2 catalysts were applied to the high temperature shift reaction with 500 ppm H2S. In the presenceof H2S, the catalysts were deactivated with time on stream due to the poisioning of H2S. Sulfurtolerancein high temperature shift activity depended upon the oxygen storage capacity of the catalysts. The regeneration rate of the catalysts was also related with the oxygen storage capacity. In addition, thePt dispersion matched the oxygen storage capacity trend. The oxygen storage capacity is a main functionto determine the sulfur tolerance in high temperature shift activity compared to the dispersion of Pt.
Keywords: CeO2/ZrO2 ratio; Oxygen storage capacity; Water gas shift; High temperature shift activity; Sulfur poisoning